Biaxial strength under fatigue of 4YSZ: Surface treatment and resin cement viscosity effects - Kétlin Fagundes Teixeira; Fernanda Cocco; Pablo Machado Soares; Gabriel Kalil Rocha Pereira; Cornelis Johannes Kleverlaan; João Paulo Mendes Tribst; Luiz Felipe Valandro; Ana Carolina Cadore-Rodrigues (PLoS ONE, 2026)
This study aimed to investigate the effect of different surface treatments combined with high- or low-viscosity resin cements on the biaxial flexural strength of 4YSZ ceramics. Discs of 4YSZ (IPS e.max ZirCAD MT, Ivoclar AG; 15 mm diameter, 1.2 mm thickness) were prepared, subjected to CAD/CAM milling simulation using #220 silicon carbide papers, and divided into 10 groups according to two factors: “Surface Treatment” – Control (CTRL, no treatment); air abrasion with 45 µm (AB45) or 110 µm (AB110) alumina oxide particles; and glaze either followed (GLZ + HF) or not (GLZ) by 10% hydrofluoric acid; and “Resin Cement Viscosity” – High (H) or Low (L). The discs were treated, luted with resin cement, and subjected to two monotonic tests (n = 2) to determine fatigue parameters, followed by biaxial fatigue testing (n = 15; piston-on-three-balls; 20 Hz; 10,000 cycles; initial stress: 75 MPa; increments of 25 MPa). Topography, fractography, and surface roughness analyses were also performed. Surface treatment significantly influenced fatigue performance (p < 0.05, F = 60.25), whereas resin cement viscosity and its interaction with surface treatment did not show significant effects (p > 0.05, F = 0.86; p > 0.05, F = 0.07). The GLZ groups exhibited the highest flexural strength (H/L-GLZ: 382–396 MPa), followed by intermediate values in CTRL (H/L-CTRL: 285–288 MPa), AB45 (H/L-AB45: 310–315 MPa), and GLZ + HF (H/L: 273–280 MPa), while AB110 groups presented the lowest strength (H/L: 205–210 MPa). Surface roughness was lower for GLZ (Ra: 1.44 µm) and GLZ + HF (Ra: 1.38 µm) compared to AB45 (Ra: 1.83 µm) and AB110 (Ra: 1.69 µm). GLZ produced smooth and homogeneous surfaces, GLZ + HF led to areas partially exposed by acid, and AB110 caused more pronounced surface defects than AB45. Hence, the GLZ treatment offered superior fatigue performance; AB45 and GLZ + HF showed behavior similar to CTRL, whereas AB110 impaired mechanical performance. Resin cement viscosity had no significant influence on fatigue strength